Tổng hợp anatat kích thước nano bằng phương pháp siêu âm hóa học - Khoai, Nguyen (Vietnam Journal of Chemistry, 2014)
Synthesis of anatase spherical particles by ultraound assisted alkali hydrolysis of anatase was investigated. The dispersion of anatase in NaOH solution was treated by ultrasound with 2.5 MHz. The obtained anatase was characterized by XRD, SEM, and SEM. Sonochemistry treatment enhances chemical reactivity of anatase solid surface with NaOH. The sonochemistry treatment with acoustic cavitations pulverized the raw anatase into nanometer size. The present process with low cost starting materials and simple operation makes possible to prepare relatively large quantities and high yield of nano structured titanate.